Unutar i izvan akademije: žene, feminizam i etnologija u Hrvatskoj - Potkonjak, Sanja (2006)
Feminist anthropology, anthropology of women, feminist ethnography, or ethnographic feminism has been reorganizing the discipline for more than thirty years in Western Academia. It has been defined differently as historical materialist analysis of gender relations, ethnographic project on women’ s everyday life ; anthropological voicing of women, a discipline which deals with cross-cultural analysis of biological and cultural construction of masculinity and femininity as well as sexuality ; branch of anthropology which deals with political and social consequences of treating women as second sex ; sinestatic discipline which combines feminism as a social movement and philosophy with innovative stile of writing, approaching field and field subjects in classical anthropological work. Contingent in its scope, interdisciplinary in its background, critical in its aims women/gender studies have had hard time in its attempt to integrate themselves into Croatian Academia. As late as the 1995s, following the collapse of communism and war atrocities in the region, feminist discourse has been sensitizing social sciences and humanities bridging the gap in between activism and scholarship ; impersonated in female scholars who joined the civil scene ; non governmental organization. Meanwhile the conventional ethnography (of continental scholarly background) has been looking at changes, mainly finding its way out of ethnology and becoming more closely related to cultural anthropology. Most recently, courses on feminist anthropology have intersected mainstream anthropological curricula in Croatia- appropriating integrationist rather than autonomous strategies. Paper deals with the female authorship in Croatian ethnography from it conception, in the late 19th century, to the current times. By showing wide range of formal and informal modes of “ professing feminism” , paper aims to explore the trajectories of feminism/ethnology relationships in Croatia.
ENG